Efesiensi Perahu Motor dalam Penghematan Waktu dan Biaya Hidup Pengguna Jasa Penyeberangan di Desa Taeng Kecamatan Pallangga Kabupaten Gowa - Tamira Tamira; Ibrahim Abbas; Erman Syarif (UNM Geographic Journal, 2020)
This research aims to know: (1) how much time can be saved by the users of river crossing services in the Taeng village of, Pallangga districts in Gowa Regency, (2) to fine out how much cost can be saved by the users of river crossing services in the Taeng village of, Pallangga districts in Gowa Regency. The study is a descriptive  research. The population in this study is the users of river crossing services in the Taeng village of, Pallangga districts in Gowa Regency. This study used accidental sampling technique. The method of data collection is observation interview and documentation techniques. The result of the research shows that: (1) efficiency of motorboat in saving of time is perceived by users or river crossing service that using bike, and the saving of time that is felt at least 20 minutes to get to the location, (2)The efficiency of motorboat in cost saving are felt by pedestrians, cost saving that can be saved by IDR 26.000 in the once of the way place of destination.